Occurrence and molecular characterization of wheat streak mosaic virus in wheat in Serbia - Vučurović, Ana; Stanković, Ivana; Katarina Zečević,; Petrović, Branka; Delibašić, Goran; Krstić, Branka (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
The wheat streak mosaic virus (WSMV), vectored by the wheat curl mite, is globally distributed and threatens wheat production worldwide. Since its fi rst occurrence in Serbia in the 1960s, WSMV presence has not been monitored. In 2019, a total of 62 samples of five wheat cultivars from eight locations in Serbia were collected and tested for the presence of nine common wheat viruses: WSMV, barley yellow dwarf virus-PAV, -MAV,  -SGV, and -RMV, cereal yellow dwarf virus-RPV, wheat spindle streak virus, brome mosaic virus, and soil-bornewheat mosaic virus, using individual or multiplex RT-PCR. WSMV was detected in 58.1% of the tested samples in seven wheat crops at fi ve diff erent locations. Species-specifi c primers failed to detect the presence of the other eight tested viruses. For further confirmation of WSMV, RT-PCR with the WS8166F/WS8909R primers covering the coat protein (CP) gene was carried out for both amplifi cation and sequencing. The amplified product of the correct predicted size (750 bp) derived from four selected isolates, 98-19, 99-19, 102-19 and 120-19, was sequenced and deposited in GenBank (MT461299, MT461300, MT461301 and MT461302, respectively). Serbian WSMV isolates showed very high nucleotide identity (98.16-99.02%) and shared a deletion of triplet codon GCA at nucleotide position 8412-8414 resulting in deletion of glycine amino acid (Gly2761). Phylogenetic analysis conducted on CP gene sequences revealed the existence of four clades, named A, B, C and D, and one recently introduced clade B1. All Serbian wheat WSMV isolates grouped into clade B together with other European isolates and one isolate from Iran. The results of this study provide the fi rst insight into molecular characterisation of Serbian WSMV isolates, indicating their close relationship with other European isolates and existence of a single genotype in the country. Phylogenetic analysis also confirms the dispersal of WSMV isolates throughout Europe from a single locus.
Keywords: wheat streak mosaic virus; wheat; RT-PCR; molecular characterization; phylogeny; Serbia